Integrating Sustainability into Indonesia’s Mining Regulation: A Normative Assessment of Downstreaming, Reclamation, and ESG Policies (Lembaga Contrarius Indonesia, 2026)
The growth of the mining sector in Indonesia has contributed significantly to national economic development, but it has also imposed serious environmental externalities. In response, the central government has enacted policies such as downstreaming mandates, post-mining reclamation requirements, and the promotion of Environmental, Social, and Governance (ESG) principles to promote green mining. This study evaluates the extent to which these policies embed sustainability principles and provide legitimate environmental protection in the mining sector. Using normative legal research, we analyze mining, environmental, and green mining regulations, supported by qualitative examination of policy implementation reports. We find that although sustainability dimensions are formally incorporated, policy execution faces major constraints: (1) downstreaming focuses heavily on economic interests with insufficient environmental controls, (2) reclamation obligations are often weakly supervised, and (3) ESG implementation remains voluntary, reducing legal certainty. We recommend stronger binding ESG regulation, integration of downstream policy with environmental instruments, and establishment of transparent oversight.